2005
DOI: 10.1248/bpb.28.1844
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Activity, Toxicology and Histopathology of Opuntioside-I and Methanolic Extract of Opuntia dillenii

Abstract: Methanolic extract of Opuntia dillenii cladodes and its pure compound a a-pyrone glycoside, opuntioside-I showed potent hypotensive activity in normotensive rats. Both the extract and opuntioside-I showed comparable effect of 44-54% fall in Mean Arterial Blood Pressure (MABP) at the dose of 10 mg/kg. No mortality was observed in rats even at the doses of 1000 mg/kg/d and 900 mg/kg/d per oral of extract and opuntioside-I respectively. However, histopathology revealed adverse effects of high doses on liver and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Studies have established that alterations in the transport capacity of the hepatocytes attributable to hepatic injury lead to leakage of enzymes from cells to the bloodstream [20]. This outcome corroborates the ndings of Saleem et al (2005) [21] and Zouhir et al (2015) [22] who reported similar increase in rats given methanolic and aqueous extract of Opuntia fi cus indica and Opuntia dillenii, respectively, though not in line with Ncibi et al (2008) [23] and Brahimi et al (2011) [24].…”
Section: Discussionsupporting
confidence: 67%
“…Studies have established that alterations in the transport capacity of the hepatocytes attributable to hepatic injury lead to leakage of enzymes from cells to the bloodstream [20]. This outcome corroborates the ndings of Saleem et al (2005) [21] and Zouhir et al (2015) [22] who reported similar increase in rats given methanolic and aqueous extract of Opuntia fi cus indica and Opuntia dillenii, respectively, though not in line with Ncibi et al (2008) [23] and Brahimi et al (2011) [24].…”
Section: Discussionsupporting
confidence: 67%
“…Recently, significant anti-diabetic and anti-glycated effects of the polysaccharides from the cladodes of O. monacantha from China have been described (Yang et al, 2008;Zhao, Yang, Yang, Jiang, & Zhang, 2007). Cactus fruits and cladodes, specially those from Opuntia genus, have been widely used as food and in folk medicine, possessing several pharmacological and nutritional properties (Feugang, Konarski, Zou, Stintzing, & Zou, 2006;Kim et al, 2006;Saleem et al, 2005;Stintzing & Carle, 2005;Stintzing & Carle, 2007). In Brazil, three species of Opuntia (sensu stricto) (Taylor, Stuppy, & Barthlott, 2002), usually called ''palmas", can be found.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of such instances in cattle, the main clinical signs were decreased appetite, colic, ruminal and intestinal hypomotility, dehydration, and increased heart rate. Methanolic extracts of a Middle Eastern Opuntia species or its glycoside, opuntioside I, given to rats produced a marked reduction in arterial blood pressure but no other adverse effects except hepatic degeneration with quite high dosage (Saleem et al 2005). Methanolic extracts of a Middle Eastern Opuntia species or its glycoside, opuntioside I, given to rats produced a marked reduction in arterial blood pressure but no other adverse effects except hepatic degeneration with quite high dosage (Saleem et al 2005).…”
Section: Opuntia Millmentioning
confidence: 99%